Live Streaming as a Catalyst: How Hedonic and Utilitarian Shopping Drive Impulse Buying Among Gen Z in Indonesia - I Gusti Ayu Tirtayani; Gusti Ayu Aghivirwiati; Wan Mohd Hirwani Wan Hussain (MIX: JURNAL ILMIAH MANAJEMEN, 2026)
Objectives: This research investigates the influence of hedonic shopping and utilitarian shopping on impulse buying behavior among Generation Z in Indonesia, by also considering the role of live streaming shopping in moderating the relationship between these two types of shopping and impulse buying.Methodology: Through data analysis from 300 respondents.Finding: The findings show that both hedonic shopping and utilitarian shopping have a positive and significant influence on impulse buying. Apart from that, live streaming shopping was also found to have a significant influence in strengthening the relationship between these two types of shopping and impulse buying behavior.Conclusion: The implications of these findings are the importance of developing more effective marketing strategies, increasing consumer awareness about the risks of impulse buying, and opportunities for further research in understanding consumer behavior in the digital era.